Desert Capitalism: Maquiladoras in North America's Western Industrial Corridor - Hellman, Judith Adler (Labour / Le Travail, 1997)
The article reviews the book, "Desert Capitalism: Maquiladoras in North America's Western Industrial Corridor," by Kathryn Kopinak.
Keywords: BOOKS -- Reviews; Capitalism; DESERT Capitalism: Maquiladoras in North America's Western Industrial Corridor (Book); KOPINAK, Kathryn; Nonfiction